Modelo para concepção de sistema de medição de desempenho do processo de desenvolvimento do produto - Prancic, Eduard (2008)
The development of a performance measurement system raises challenges related to both its role of application, involving the decision makers, and its range over the organization processes. Some processes are not yet properly incorporated in the literature on performance measurement systems, at least not in a structured and well articulate way, being usually represented only by a group of performance indicators. One of these processes is the Product Development Process (PDP)whose relevance given both by the academy and by the corporations justifies an investigation on how a performance measurement system should be developed to facilitate the appropriate use in search of speed and efficiency in new product development. Within this context, this thesis deals with two major subjects within Production Engineering simultaneously approached: a model for developing performance measurement systems to support product development process management. Such model has also the intent of highlighting the constraints and restrictions involved in performance systems structure and implementation. For this purpose a literature review was carried out. It has pointed out a gap in dealing with these two subjects simultaneously in Production Engineering field. A model was built considering the literature review on the subjects and also empiric evidences collected from four companies in several business segments. A multiple case study took into account the prospective of using performance measurement in different hierarchical levels. Furthermore, during the visits to the mentioned companies, important aspects were revealed regarding to the development of the performance measures and the articulation among these measures. Aspects as organizational structure, business model and competitive scenery, PDP management framework and information technology, all influence and impact the performance measurement systems development. However, in the studied companies, very few performance indicators were found, different from the traditional "cost, time and quality .